Fenomena Profil Wanita Dalam Fotografi Glamor - Moedjisoewasto Moedjisoewasto (Ornamen, 2010)
Female has a unique complexity in generating a nice and attractive picture because all things such as hair, make-up, costume (dress) must be suitable and proper. While, male is not very demanded to be perfect in his appearance, it may be said, he has a tendency that it is better to appear in simplicity  In other hand, to dress a female, various accessories and anything are needed to make her more attractive. If we are seeing glamorous photographs, we often saw good-looking female appearances with their lovely and energetic dresses, and perhaps, they were posing in important and happy moments such as an entertainment event, fashion event, commercial illustration, or art performance. For me, glamour is a miracle. It is about a yearning of a female to be perpetuated (in an im  age or a photograph), in a setting in which she is a most beautiful and adorable object (model), and at the same time, she is being a center of attentive attempts of the event. Therefore, it is a dream (fantasy) of her to make herself becomes more than her genuine appearance. With an expectation that, for a moment, she is a superstar, a princess, a dream (a fantasy world).  Key words: Glamour, beautiful and adorable model, fantasy world